The analysis of functional capacity of people with tetraplegia during the 1st level of the Active Rehabilitation camp. - Jozefowsky Peter; Bolach Bartosz; Prystupa Tetyana (Kharkov National Pedagogical University, 2011)
The aim of the study was to analyze functional capacity during the 1st level of the Active Rehabilitation camp of people after spinal cord injury (SCI) in cervical segment. The individual functional indicators as: self-service, sphincter control, mobility, locomotion and communication have been analyzed. The study included 30 men with SCI in cervical segment and in age of 18-45. The clinimetric scale for functional rating of neurological patients - The Functional Indicator "Repty" was used in the study. The test were conducted twice: immediately before the beginning of the camp and after. An improvement in functional capacity occurred among all respondents during the 1st level of the AR camp. The greatest improvements concerned the mobility and self-service, smaller improvement occurred in locomotion and sphincter control. There was no significant improvement in level of communication.